2020
DOI: 10.3390/molecules25061267
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Therapeutic Promise of Flavonoids against Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the utmost chronic neurodegenerative disorders, which is characterized from a neuropathological point of view by the aggregates of amyloid beta (Aβ) peptides that are deposited as senile plaques and tau proteins which form neurofibrillary tangles (NFTs). Even though advancement has been observed in order to understand AD pathogenesis, currently available therapeutic methods can only deliver modest symptomatic relief. Interestingly, naturally occurring dietary flavonoids have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 254 publications
(279 reference statements)
1
51
0
Order By: Relevance
“…Flavonoids have been extensively used in traditional herbal medicine [ 24 ], having important biological effects associated to a wide spectrum of pharmacological activity. They play preventive and therapeutic roles in several pathological processes like arthritis [ 25 ], neurodegenerative [ 26 , 27 , 28 ] and cardiovascular processes [ 29 ], cancer [ 30 ], or pain [ 31 , 32 ]. Several studies revealed that the biological actions of some flavonoids are in part mediated by their ability to modulate the activity of some ion channels, for instance, the cholinergic nicotinic channels.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids have been extensively used in traditional herbal medicine [ 24 ], having important biological effects associated to a wide spectrum of pharmacological activity. They play preventive and therapeutic roles in several pathological processes like arthritis [ 25 ], neurodegenerative [ 26 , 27 , 28 ] and cardiovascular processes [ 29 ], cancer [ 30 ], or pain [ 31 , 32 ]. Several studies revealed that the biological actions of some flavonoids are in part mediated by their ability to modulate the activity of some ion channels, for instance, the cholinergic nicotinic channels.…”
Section: Resultsmentioning
confidence: 99%
“…In healthy people, Aβ production rate (ie, 7.6%) is normally lower than its rate of clearance (ie, 8.3%) per hour. 8 In AD, APP is processed by βfollowed by γ-secretases, resulting in amyloidogenic pathway and causing the formation of Aβ protein fragments of 40 (Aβ 40 ) or of 42 (Aβ 42 ) amino acid length. As this latter can aggregate in insoluble amyloid fibrils, when the ratio between Aβ 42 /Aβ 40 is imbalanced towards Aβ 42 , oligomers formation prevails, extracellular amyloid plaques are deposited and, in turn, synaptic structure and plasticity alterations sustained a cognitive decline.…”
Section: Ad Pathophysiological Main Hypothesismentioning
confidence: 99%
“…Data showed how resveratrol could reach the brain and inhibit the formation and aggregation of Aβ peptides. 8,85 Another very interesting flavonoid is quercetin. Its applications are best studied in targeting cancer.…”
Section: Nutraceutical Loaded Nps and Green Npsmentioning
confidence: 99%
“…Hyperphosphorylation and aggregation of tau is another major hallmarks of AD ( Uddin et al., 2020h : Uddin et al., 2020g ). Accumulating evidence suggested that cannabinoids also play a significant role in tau pathology.…”
Section: Effect Of Cannabinoids On Alzheimer’s Hallmarksmentioning
confidence: 99%